2013
DOI: 10.1128/jvi.02002-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CUL4A Neddylation Causes a Reversible Block to SAMHD1-Mediated Restriction of HIV-1

Abstract: The deoxynucleoside triphosphohydrolase SAMHD1 restricts retroviral replication in myeloid cells. Human immunodeficiency virus type 2 (HIV-2) and a simian immunodeficiency virus from rhesus macaques (SIVmac) encode Vpx, a virion-packaged accessory protein that counteracts SAMHD1 by inducing its degradation. SAMHD1 is thought to work by depleting the pool of intracellular deoxynucleoside triphosphates but has also been reported to have exonuclease activity that could allow it to degrade the viral genomic RNA or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Recently, we and other groups discovered that posttranslational modification by neddylation is critical for Vpx-CRL4 (DCAF1) E3 ligase function (59)(60)(61). A neddylationactivating enzyme (NAE) inhibitor, MLN4924, inhibited the neddylation of Vpx-bound Cullin4 and blocked the Vpx-induced degradation of SAMHD1 proteins (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we and other groups discovered that posttranslational modification by neddylation is critical for Vpx-CRL4 (DCAF1) E3 ligase function (59)(60)(61). A neddylationactivating enzyme (NAE) inhibitor, MLN4924, inhibited the neddylation of Vpx-bound Cullin4 and blocked the Vpx-induced degradation of SAMHD1 proteins (60).…”
Section: Discussionmentioning
confidence: 99%
“…We and other groups have recently demonstrated that the posttranslational modification process of neddylation, which is a determinant for the activation of Cullin-RING E3 ligases, is essential for the activity of the Vpx-CRL4 (DCAF1) E3 ligase (59)(60)(61). The neddylation inhibitor MLN4924 blocks Vpx function and preserves the antiviral activity of SAMHD1.…”
Section: Importancementioning
confidence: 99%
“…We have previously shown this higher-molecularweight band to be the neddylated form of CUL4 (91). Neddylation is required to activate cullin ubiquitin ligases and is also necessary for Vpr and Vpx functions through CRL4 (91,94,95). To test whether the single, slower-migrating band detected in the nucleus is indeed neddylated CUL4, we treated HEK293T cells with the neddylation inhibitor MLN4924 before subcellular fractionation.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether the degradation of the NLS.GFP.SAM595 reporter protein utilized the same pathway as the full-length SAMHD1, we tested its response to MG132, a proteasome inhibitor, and MLN4924, a neddylation inhibitor, both of which are known to inhibit Vpx function (1,2,19). We found that MG132 prevented degradation of the fusion protein and that MLN4924 partially blocked the degradation (Fig.…”
Section: Establishment Of a Cell Line For The Analysis Of Vpx-inducedmentioning
confidence: 99%
“…The activity of the CRL4 DCAF1 E3 ubiquitin ligase is regulated by the conjugation of Nedd8 to Cul4A. Inhibition of neddylation using the drug MLN4924 prevents SAMHD1 degradation (19). DCAF1 also functions in HECT-family EDD/UBR5 E3 ubiquitin ligases (re-viewed in reference 20), and HIV-1 Vpr interacts with the EDD-DDB1-DCAF1 E3 ligase complex to inhibit telomerase activity (21).…”
mentioning
confidence: 99%